Flexural behaviour of high strength engineered cementitious composites (ECC)-reinforced concrete composite beams - Fengjiang Qin; Xinyan Wei; Youfu Lu; Zhigang Zhang; Jin Di; Zhiwei Yin (Case Studies in Construction Materials, 2023)
The flexural behaviour is investigated in this paper for engineered cementitious composite (ECC)-reinforced concrete (RC) composite beams. The thickness and shape of the ECC layer are the variables studied. ECC has proved to be one of the ideal construction materials for improving the flexural capacity of reinforced conventional concrete beams. When the composite beam specimens reached the load-bearing limit state, only dense micro-cracks appeared in the ECC layer in the tensile zone, and no local fracture was observed in the test, reflecting the high ductility of ECC. The load values for all phases of the ECC-RC composite beams are higher than those of the RC beams, suggesting that the composite beams have better ductility and energy absorption capacity. In addition, the ability of the U-shaped ECC layer composite beam to limit crack development and the synergistic effect with the reinforcement is superior compared to the other tested beams. Finally, considering the strain-hardening characteristics of ECC, based on the force equilibrium conditions, the formulae are derived for the flexural capacity of ECC-RC composite beams.